Digital transformation: theoretical backgrounds of digital change - Tratkowska, Kamila (Transformacja cyfrowa: teoretyczne aspekty zmian cyfrowych, 2019)
The purpose of this paper is a review of the existing deﬁnitions of digital transformation (abbrev. DT) and to structure its implications for new business models and implementation activities. This article was inspired by literature review whose main aim was to provide insight into the understanding of the theoretical background of digital transformation by means of the digitization and current megatrends in the VUCA world. The author gives examples, completes the literature research and shows the theoretical aspects of concepts, as well briefly analyzes the trends concerning DT. The article starts from definitions of DT, through digital readiness, to efficiency in the DT area. The main findings are that the approach for the structured digitization of business models is expanding, several excellence models have been developed over the past few years, and the implementation model for DT becomes a widely known concept. The author offers a clear deﬁnition, which corresponds to phases for DT of business models using a Digital Capability Maturity Models overview. Moreover, this paper is the author’s declaration of further DT’s research in its practical dimension
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 4. s. 32-37
Keywords: digital transformation; digitalization; VUCA; digital maturity model; transformacja cyfrowa; digitalizacja; model dojrzałości cyfrowej